Performance evaluation of recycled rubber waterproofing bituminous membranes for concrete bridge decks and other surfaces. (1st April 2017) - Mazzotta, Francesco; Lantieri, Claudio; Vignali, Valeria; Simone, Andrea; Dondi, Giulio; Sangiorgi, Cesare
Highlights: A new waterproofing rubberized membrane for the protection of concrete bridge deck is proposed. The waterproofing membrane is composed of a mat sandwiched between two layers of SBS-modified bitumen. An extensive laboratory characterization confirms the product characteristics and the overall performances. Abstract: In this paper a green waterproofing membrane for the protection of concrete decks is proposed. It is composed of a recycled rubber mat, sandwiched between two layers of SBS-modified bitumen. The rubber mat, itself, provides advantages in terms of environmental impact, because it is composed by a high density elastic mat made with granular rubber coming from the recycling of End of Life Tires, stuck with isocyanate and pressed. The polymer modified bitumen improves the interfaces adhesion and bonding, providing to the system a good water resistance. The rubber mat, different from the most common waterproofing membranes, is not supplied in rolls but can be applied in layers directly in work, according to the area to be covered. Laboratory characterization and a comparison to manufacturer's limiting values and tolerances of other available membranes confirm the overall performance and the use conformity of the proposed system.